(3cJGH GdYRdI hGdEfaQGOs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3CMeO Hf YHO Gddg Hf CHj GdZfGFe GdeSde Hf MeGO Hf ejSQI GdGQOi s)
(3ChdgG (B:s
(3CNHQfG CHh GdMSf Hf CHj YHO Gddg Hf CHj GdMSf bGd YbHI Hf YGeQ bdJ jG QShd Gddg eG GdfLGI ? bGd (B: ( (3Cedc Ydjc dSGfc hdjSYc HjJc hGHc Ydi NWjFJc (B) s
(3BNQgG (B:s
(3Edi eG fOH Gddg Edjg GdeDefjf ef GdWGYI hJQc GdeYUjI aEfc JNQL ef MjQJc hJQLY Yf LgGdJc heG CTcd Ydjc aQOg Edi YGdeg hdG bhg EdG HGddg GdYdi GdYXje s
(3GdfSNI HgG MhGTs
(3fbdJ Yf fSNI UMjMI hYdjgG SeGYGJ fbd GdcGJH UhQJgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs